Selective assertiveness and strategic deference: explaining judicial contestation of military prerogatives in Pakistan. Issue 3 (3rd April 2021) - Kureshi, Yasser
ABSTRACT: How do we explain variation in judicial assertiveness towards politically powerful militaries? This article argues that the judiciary's willingness to assert itself against the military is contingent upon the type of military prerogative being challenged. Focusing on Pakistan, I find that courts are more willing to contest military prerogatives connected to the military's political authority, than prerogatives connected to its institutional autonomy. This selective assertiveness is strategic, as concerns about military retaliation against the judiciary are more likely to outweigh judicial preferences, on questions of the military's institutional autonomy than on questions of the military's political authority. I test this hypothesis using an original dataset of 720 high court and supreme court judgments pertaining to military prerogatives from Pakistan. I then discuss a sample of judgments selected from the dataset to demonstrate how variation in judicial assertiveness is guided primarily by strategic concerns about the likelihood of military retaliation against the judiciary. In studying the interactions between the judiciary and the military in Pakistan, the article provides a new perspective on the sources of judicial assertiveness and restraint, and the role the judiciary can play in bringing militaries under civilian control in authoritarian and post-authoritarian states.